Computer modeling and research of the stress-deformed state of the system "dental implant - bone tissue" - Hrynkiv, B.I.; Borushchak, L.O.; Ozhogan, Z.R.; Miziuk, L.V.; Ozhogan, R.Z.; Viklyuk, I.V. (Physics and Chemistry of Solid State, 2026)
The nature of the stress-deformed state of the system "dental implant - bone tissue" was determined using three-dimensional computer models that were created in the solid-state parametric modeling program Solid Works 2024 using the finite element method. The actual research was performed using the Simulation package. Using the Solid Works 2024 program, solid-state parametric models were developed, which included a fragment of the jaw bone with a dental implant and orthopedic elements. The study used physical and mechanical parameters of orthopedic elements (crown and abutment), dental implant, cortical and trabecular bone tissue of the jaws. The study of the stress-strain state was carried out under the condition of average strength and density of trabecular bone tissue of the jaws. During the study, conditions were created for the maximum asymmetric application of chewing load force to orthopedic elements and dental implant, which allowed to identify unfavorable conditions for the functioning of the crown - implant - bone tissue system.